2016
DOI: 10.1186/s12885-016-2138-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-c-Met monoclonal antibody ABT-700 breaks oncogene addiction in tumors with MET amplification

Abstract: Backgroundc-Met is the receptor tyrosine kinase for hepatocyte growth factor (HGF) encoded by the MET proto-oncogene. Aberrant activation of c-Met resulting from MET amplification and c-Met overexpression is associated with poor clinical outcome in multiple malignancies underscoring the importance of c-Met signaling in cancer progression. Several c-Met inhibitors have advanced to the clinic; however, the development of inhibitory c-Met-directed therapeutic antibodies has been hampered by inherent agonistic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 26 publications
(39 reference statements)
3
69
0
Order By: Relevance
“…Note that hz224G11 also inhibits the Akt and Erk pathways, as reported elsewhere. 49 The results reported here highlight the therapeutic potential of hz224G11 for patients with HGF-driven tumors and/ or c-Met ligand-independent cancer. This is the only full antagonist IgG1 antibody reported to date with both blocking activities and ADCC functions, making it arguably the best molecule in its class.…”
Section: Discussionsupporting
confidence: 51%
“…Note that hz224G11 also inhibits the Akt and Erk pathways, as reported elsewhere. 49 The results reported here highlight the therapeutic potential of hz224G11 for patients with HGF-driven tumors and/ or c-Met ligand-independent cancer. This is the only full antagonist IgG1 antibody reported to date with both blocking activities and ADCC functions, making it arguably the best molecule in its class.…”
Section: Discussionsupporting
confidence: 51%
“…Since gastric cancer [30,31] is a primary clinical indication for ABT-700 [18,21,29], the ability to improve outcome upon combination with the SoC agent CPt was evaluated. The combination of ABT-700 and CPt was evaluated using the same progressively increasing initial tumor burden scheme as described previously.…”
Section: Resultsmentioning
confidence: 99%
“…The primary clinical indication for ABT-700 is gastric carcinoma [18,21,29] and hence the majority of mechanistic studies were performed using the gastric cancer model Hs 746T. To determine the degree of antibody-receptor engagement necessary for activity, Fab and F(ab') 2 fragments of ABT-700 were generated and evaluated using proliferation assays as a readout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead patient selection strategies to identify those tumors in which MET is constitutively activated through gene amplification, mutation, or ligand-dependent activation may be necessary to predict sensitivity to many of these inhibitors (14,15). Consistent with reliance on MET activation for activity, ABT-700, a c-Met-targeting antibody without the agonist activity associated with many c-Met antibodies, was well tolerated in a phase I trial and demonstrated antitumor activity in select patients with MET-amplified solid tumors (16,17). Although increased frequencies of MET amplification may be associated with relapsed/refractory tumors including those with EGFR-activating mutation in non-small cell lung cancer (NSCLC), primary MET genomic amplification is a low frequency event in most tumors (1%-5%), thereby limiting the patient population where inhibitors that block MET signaling may be effective (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%